2018
DOI: 10.1177/0284185118786063
|View full text |Cite
|
Sign up to set email alerts
|

Elastography and diffusion-weighted MRI in patients with testicular microlithiasis, normal testicular tissue, and testicular cancer: an observational study

Abstract: Background Ultrasound elastography is increasingly available in clinical practice. Recent studies showed higher velocity stiffness in testicular tumors compared to normal testicles. Purpose To evaluate ultrasound elastography in combination with the apparent diffusion coefficient measurements in diffusion weighted (DW) magnetic resonance imaging (MRI) in testicles. DW can be a useful tool in evaluating testicular malignancies. However, the relationship between velocity stiffness and MRI diffusion is not well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Aging, neoplasia, and metabolic diseases can lead to fibrosis and an increase of tissue stiffness 5 . Thus, tissue stiffness is a clinically relevant parameter for diagnosis and prognosis purposes, as we have here shown that alteration of this mechanical parameter is coupled with the progression of diseases and malignancies associated with kidney cancer and fibrosis 143 , PCa 177 , 178 , bladder cancer 167 , testicular cancer 189 , and infertility related diseases 190 192 . Biochemical, topographical, and mechanical modification of the ECM occurs both at the primary and metastatic site 19 , 21 , 26 , but there is also an important cellular contribution to the altered tissue stiffness by means of cell density, contractility, and traction 82 , 93 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Aging, neoplasia, and metabolic diseases can lead to fibrosis and an increase of tissue stiffness 5 . Thus, tissue stiffness is a clinically relevant parameter for diagnosis and prognosis purposes, as we have here shown that alteration of this mechanical parameter is coupled with the progression of diseases and malignancies associated with kidney cancer and fibrosis 143 , PCa 177 , 178 , bladder cancer 167 , testicular cancer 189 , and infertility related diseases 190 192 . Biochemical, topographical, and mechanical modification of the ECM occurs both at the primary and metastatic site 19 , 21 , 26 , but there is also an important cellular contribution to the altered tissue stiffness by means of cell density, contractility, and traction 82 , 93 .…”
Section: Discussionmentioning
confidence: 80%
“…The stiffness of testicular cancer can be more than double the stiffness of normal testis, suggesting that increased stiffness could be used as a testicular malignancy marker, and detectable by ultrasound elastography 188 , 189 . In testicular microlithiasis, a modest increase of tissue stiffness compared to normal testicles was measured by SWE 188 , but no malignant characteristics are measured by SWE or MRI diffusion in this condition (stiffness values reported in Table 2 ) 189 . Thus, benign testicular lesions can be differentiated from malignant ones both by MRI diffusion and elastography.…”
Section: Organ-specific Stiffnessmentioning
confidence: 99%
“…The literature search found a total of 1106 articles (tumors, n = 584; acute scrotum, n = 193; undescended testes, n = 178; and infertility, n = 151). Ultimately, 83 articles were deemed relevant and used as the literature basis of this review (tumors, n = 50; acute scrotum, n = 6; undescended testes, n = 7; and infertility, n = 20) 6–9,13,24–33,35,43,48–110 . The flow chart of the selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…24 DWI by assessing the microscopic diffusion movements of water molecules in testicular tissue, greatly improves the diagnostic efficiency of MRI in the detection and characterization of intratesticular lesions. 50,51,[55][56][57]63,72 Testicular malignancies often present with restricted diffusion and a lower apparent diffusion coefficient (ADC) value, when compared to normal testis and benign intratesticular lesions (Figure 4). A cut-off ADC of 0.99 × 10 −3 mm 2 /s has been reported reliable for the characterization of intratesticular lesions, with a sensitivity of 93.3%, specificity of 90%, PPV of 87.5%, and NPV of 94.7%.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…Pedersen et al also discovered a correlation between SWE and MRI-DWI values, meaning that within stiff lesions a higher impediment to water molecules diffusion is present. 53 Marcon et al found that stiffness of focal testicular lesions is increased in comparison with normal parenchyma both at SWE and VTIQ, with the values of the latter being higher than the ones of the former, because of technical differences between the two methods. 55 Some authors made further research trying to discriminate benign from malignant lesions using SE; they had good feedbacks although controversial.…”
Section: Discussionmentioning
confidence: 99%